Organic Fertilization Effects on Physicochemical and Nutritional Parameters of Wheat Grain: A Comprehensive Review - S. B. Bhosale (The Bioscan, 2025)
Wheat (Triticum aestivum L.) is a globally important staple crop that provides essential carbohydrates, proteins, fiber, minerals, and vitamins to human diets. However, the widespread use of chemical fertilizers in wheat cultivation has raised concerns related to soil degradation, nutrient-use inefficiency, and chemical residue accumulation in food products. Organic fertilization offers a sustainable alternative by enhancing soil biological activity, improving nutrient cycling, and supporting gradual nutrient release throughout the plant growth cycle. This review synthesizes findings from recent studies to evaluate how organic fertilization influences the physicochemical properties and nutritional composition of wheat grain. Evidence indicates that organic amendments such as farmyard manure, vermicompost, green manures, and biofertilizers increase soil organic carbon, microbial biomass, and enzyme activities, leading to improved root development, efficient nutrient uptake, and enhanced grain filling. Wheat grown under organic fertilization commonly exhibits higher protein quality, enriched mineral content (particularly Fe, Zn, and Ca), and increased dietary fiber, along with reduced pesticide and chemical residues. Although organic systems may initially result in lower yields during the transition phase, yield stability typically improves over time as soil structure and fertility are restored. Overall, organic fertilization not only enhances grain nutritional quality but also promotes environmental sustainability, making it a valuable approach for resilient wheat production systems. KEYWORDS: Organic fertilization; Wheat grain quality; Soil health; Nutritional composition; Sustainable agriculture.